Effect of Planned Nursing Interventions on the Prevention of Acute Urinary Retention (AUR) in Male Patients after Cardiac Catheterization - Mahnaz khatiban (Hamadan University of Medical Sciences, 2017)
Introduction: With the increasing use of cardiac catheterization and its complications, such as urinary retention, finding a safe and non-invasive way to solve this problem is essential. The aim of this study was to evaluate the impact of planned nursing interventions on prevention of acute urinary retention in male patients, following cardiac catheterization, at educational and health centers of Hamadan city.